Queer judgments : homosexuality, expression, and the courts in Canada - MacDougall, Bruce, 1960- (University of Toronto Press, 2000)
Chapter 15 of Canada's Charter of Rights and Freedoms now states that it is unconstitutional to discriminate on the basis of race, class, or sexual orientation. Although the letter of the law has been changed with regard to homosexuality, has the spirit of the people who implement the law been transformed as well?Judicial response to cases concerning the rights of lesbians and gay men - decisions and the language used in the ruling - has a profound impact on social perceptions. Bruce MacDougall sifts through hundreds of reported and unreported cases of the past four decades in order to uncover the subjective assumptions and biases operating in the courts. In his examination of issues including gay bashing, homosexuality and the school system, outing, and pornography the author exposes the insidiousness of homophobia in society. MacDougall also assesses the impact of individual judges on Canadian society. This study examines the rhetoric of judicial expression in connection with a vast array of material on the subject of homosexuality. MacDougall's style is refreshingly conversational, and "Queer Judgments", with its critical perspective, celebrates the reforms that have been achieved and suggests strategies for social change